Metagenome and metabolism: the tissue microbiota hypothesis. (4th September 2013) - Burcelin, Rémy; Serino, Matteo; Chabo, Chantal; Garidou, Lucile; Pomié, Celine; Courtney, Michael; Amar, Jacques; Bouloumié, Anne
Abstract : Over the last decade, the research community has revealed the role of a new organ: the intestinal microbiota. It is considered as a symbiont that is part of our organism since, at birth, it educates the immune system and contributes to the development of the intestinal vasculature and most probably the nervous system. With the advent of new generation sequencing techniques, a catalogue of genes that belong to this microbiome has been established that lists more than 5 million non‐redundant genes called the metagenome. Using germ free mice colonized with the microbiota from different origins, it has been formally demonstrated that the intestinal microbiota causes the onset of metabolic diseases. Further to the role of point mutations in our genome, the microbiota can explain the on‐going worldwide pandemic of obesity and diabetes, its dissemination and family inheritance, as well as the diversity of the associated metabolic phenotypes. More recently, the discovery of bacterial DNA within host tissues, such as the liver, the adipose tissue and the blood, which establishes a tissue microbiota, introduces new opportunities to identify targets and predictive biomarkers based on the host to microbiota interaction, as well as to define new strategies for pharmacological, immunomodulatory vaccines and nutritional applications.